Advising Practices in Postgraduate Programs and Doctoral Students’ Satisfaction - Sheila Hamburg; Adriana Satico Ferraz; Ana Paula Porto Noronha; Acácia Aparecida Angeli dos Santos (Paidéia (Ribeirão Preto), 2024)
Abstract: Academic advising in Stricto Sensu Postgraduate Programs is associated with postgraduate student satisfaction. Hence, this research aimed to investigate the relationship between the variables found in the advising process and the levels of doctoral students’ satisfaction resulting from these practices. Postgraduate students from different educational institutions and areas of knowledge ( N = 372) completed remotely/asynchronously the Questionnaire on Good Practices for Academic Advising in Postgraduate Research. Data were analyzed using path analysis and the Kruskall-Wallis test. The results showed an association between some characteristics of the advising process (access to advising and level of demand from the advisor) and postgraduate students’ satisfaction (regarding the project, the advisor, growth opportunities, and relationships), intermediated the number of hours per month allocated to advising. The conclusion is that advising practices require further studies and discussions that can contribute to the quality of the advisor-student relationship, extending into the training of new researchers and professors.